La estrategia virtual de la Revista Raíces: promoviendo la lectura, innovando los procesos editoriales (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
As an alternative response to the hegemonic mechanism of privatization of knowledge worldwide, from Latin America and other parts of the world, the production of indexed scientific journals of open access in national and regional portals are being promoted. To reach an increasingly wide audience of Raices readers (not only specialized), a virtual strategy has been implemented that has allowed this journal to grow, increasing the number of visits to the website (from 629 visits on 03/14/2017 we have reached 3.531 visits on 09/29/2017) and the number of downloads of scientific articles (from 516 downloaded articles as of 04/04/2017 to 1253 downloaded articles as of 09/25/2017, with monthly increases of 30%). The quantitative data allows to confirm that social networks are essential to the conversion of followers into readers, and to publish the editorial initiative and its content beyond national borders. From the Revistas Facebook fan page, weve analyzed readers profiles, their origins, the schedules of connectivity and the performance of the publications in terms of people reached directly and indirectly. From the website where the Revista is hosted, the number of visits and the number of downloads of articles have been analyzed periodically. The monitoring of the metrics generated in the OJS platform and the Facebook fan page have been essential to the results to understand who our readers are and what their preferences are, at the same time, the allow us to improve the quality and relevance of our proposal.
Keywords: Virtual Strategy, altermetrics, social networks, promoting reading.